IgG4 Characteristics and Functions in Cancer Immunity - Crescioli, Silvia (Curr Allergy Asthma Rep, 2016)
IgG4 is the least abundant subclass of IgG in normal human serum, but elevated IgG4 levels are triggered in response to a chronic antigenic stimulus and inflammation. Since the immune system is exposed to tumor-associated antigens over a relatively long period of time, and tumors notoriously promote inflammation, it is unsurprising that IgG4 has been implicated in certain tumor types. Despite differing from other IgG subclasses by only a few amino acids, IgG4 possesses unique structural characteristics that may be responsible for its poor effector function potency and immunomodulatory properties. We describe the unique attributes of IgG4 that may be responsible for these regulatory functions, particularly in the cancer context. We discuss the inflammatory conditions in tumors that support IgG4, the emerging and proposed mechanisms by which IgG4 may contribute to tumor-associated escape from immune surveillance and implications for cancer immunotherapy.